Is the Retina a Mirror of the Aging Brain? Aging of Neural Retina Layers and Primary Visual Cortex Across the Lifespan - Jorge, Lília; Canário, Nádia; Quental, Hugo; Bernardes, Rui; Castelo-Branco, Miguel (Frontiers in Aging Neuroscience, 2020)
How aging concomitantly modulates the structural integrity of the brain and retina in healthy individuals remains an outstanding question. Given the strong bottom-up retinocortical connectivity, it is important to study how these structures co-evolve during healthy aging in order to unravel mechanisms that may affect the physiological integrity of both structures. For the 56 participants in the study, primary visual cortex (BA17) (as well as frontal, parietal and temporal regions) thickness was measured in T1-weighted magnetic resonance imaging (MRI), and retinal macular thickness (10 neuroretinal layers) was measured by optical coherence tomography (OCT) imaging. We investigated the statistical association of these measures and their age dependence. We found an age-related decay of primary visual cortical thickness that is significantly correlated, with a decrease in global and multiple layer retinal thickness. The atrophy of both structures might jointly account for the decline of various visual capacities that accompany the aging process. Furthermore, associations with other cortical regions suggest that retinal status may index cortical integrity in general. Keywords: Healthy aging; optical coherence tomography (OCT); Magnetic Resonance Imaging (MRI), primary visual cortex (BA17); retinal segmentation; ganglion cell layer (GCL); outer segment photoreceptor/RPE complex (OPR).